Nano drug delivery systems: a promising approach to scar prevention and treatment - Jia-Ying Ding; Lu Sun; Zhi-Heng Zhu; Xi-Chen Wu; Xiao-Ling Xu; Yan-Wei Xiang (Journal of Nanobiotechnology, 2023)
Abstract Scar formation is a common physiological process that occurs after injury, but in some cases, pathological scars can develop, leading to serious physiological and psychological effects. Unfortunately, there are currently no effective means to intervene in scar formation, and the structural features of scars and their unclear mechanisms make prevention and treatment even more challenging. However, the emergence of nanotechnology in drug delivery systems offers a promising avenue for the prevention and treatment of scars. Nanomaterials possess unique properties that make them well suited for addressing issues related to transdermal drug delivery, drug solubility, and controlled release. Herein, we summarize the recent progress made in the use of nanotechnology for the prevention and treatment of scars. We examine the mechanisms involved and the advantages offered by various types of nanomaterials. We also highlight the outstanding challenges and questions that need to be addressed to maximize the potential of nanotechnology in scar intervention. Overall, with further development, nanotechnology could significantly improve the prevention and treatment of pathological scars, providing a brighter outlook for those affected by this condition.